Small-Molecule SB216763-Loaded Microspheres Repair Peripheral Nerve Injury in Small Gap Tubulization - Rao, Feng; Yuan, Zhipeng; Zhang, Dianying; Yu, Fei; Li, Ming; Li, Dongdong; Jiang, Baoguo; Wen, Yongqiang; Zhang, Peixun (Frontiers in Neuroscience, 2019)
Given the complicated pathological process, peripheral nerve injury has not yet been well resolved. SB216763 is a small molecular compound that can enhance remyelination of peripheral nerves by inhibiting glycogen synthase kinase-3β (GSK3β). A previous study showed that GSK-3β inhibitor stimulated myelin gene expression and restored the myelin structure. Herein, we present the effect of small gap tubulization integrated with SB216763-loaded microspheres by using chitosan conduit. In vitro, SB216763 could promote DRGs axons growth. In vivo studies showed that SB216763 increased the number of myelinated axons and thickness of myelin sheaths. The electrophysiological examination and sciatic functional index results also indirectly indicated the role of SB216763 in repairing peripheral nerve injury. Meanwhile, SB216763 promoted the recovery of muscle function. In conclusion, combining SB216763-loaded PLGA microspheres with conduit small gap tubulization has promising potential applications in repairing peripheral nerve injury.